A Pilot Study to Increase Chewing in Children With Feeding Disorders. (May 2013) - Volkert, Valerie M.; Piazza, Cathleen C.; Vaz, Petula C. M.; Frese, Jana
Children with feeding disorders often display chewing deficits. Unfortunately, there is a paucity of research examining procedures to increase or teach chewing to children with feeding disorders. The few studies on this topic have utilized multicomponent treatments typically involving a shaping procedure. In addition, to our knowledge, studies on chewing have not yet incorporated a product measure of chewing (whether the food is broken down enough to swallow after chewing), which we have termed mastication . In the current investigation, we evaluated relatively simple treatments to increase chewing with two children with a feeding disorder who were not chewing at clinically acceptable levels after treatment with nonremoval of the spoon. We also developed a product measure of chewing. In Study 1, we used a least-to-most prompting plus praise procedure to increase chews per bite in a typically developing child with a feeding disorder. We then used the results of Study 1 to refine treatment and develop our mastication measure for Study 2. In Study 2, we implemented a descriptive verbal prompt and praise procedure to increase chews per bite and percentage of mastication with one child with developmental delays and a feeding disorder.